Microemulsion Containing Ellagic Acid Rich Extract and Its Characterization - Parveen1, Rashida; Akhtar1, Naveed; Abid1, Muhammad; Shair Mohammad1, Imran (Asian Journal of Chemistry, 2014)
Ellagic acid, the active component in Punica granatum extract, has been reported to have the antioxidant, anti-tyrosinase and ultra-violet induced pigmentation in the human skin effects. In this study, extract was obtained from the Punica granatum fruit rinds which were extracted by 50 % ethanol and analyzed ellagic acid by UV method at 365 nm. The percentage of ellagic acid is about 84.48 %. Microemulsions were formulated using pseudoternary phase diagram. Palm oil and water were chosen as the oil and aqueous phase, respectively. The surfactant (Tween 80) and co-surfactant (PG) were used in preparation of the microemulsion. They were mixed in different ratios (2:1 and 5:1). The results showed the region of microemulsion on the phase diagram was obtained when increase the ratio of Tween 80. Evaluation of microemulsion regarding particle size, zeta potential, conductivity, stability, viscosity, scanning electron microscopy, refractive index and pH. This study established that a stable ellagic acid rich extract containing microemulsion was used for further topical uses.